Podcast as Road Safety Education Media for Adult Drivers in Indonesia: Development and Effectiveness Using Uses and Gratifications - Azzah Ula Nabillah Yoni; Brasie Pradana Sela Bunga Riska Ayu; Hanendyo Putro (Jurnal Pendidikan Terapan, 2026)
This study developed a podcast titled "SaveDrive ID" as a road safety education medium and evaluated its effectiveness among active drivers in Indonesia. The study employed Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate). A needs analysis was conducted with 30 drivers; expert validation was performed by content and media specialists; and effectiveness was measured using Gratifications Sought (GS) and Gratifications Obtained (GO) instruments on 100 drivers at a Pertamina fuel station on Jl. Raya Narogong No. 57, Bogor. Expert validation yielded an overall feasibility score of 85.47%. GS-GO gap analysis showed positive gaps across all four dimensions: cognitive (+10.87%), affective (+8.20%), tension release (+7.87%), and personal integration (+6.00%), with an overall gap of +8.23% and mean GO score of 90.43%, all categorized as Highly Satisfying. Podcast is a viable, flexible, and impactful medium for non-formal road safety education that can reach active adult drivers without the constraints of conventional in-person delivery.